STUDENTS’ PERSPECTIVE ON THE USE OF BLOG FOR ENGLISH WRITING LEARNING - Wilanisa, Dwi Afria; Arifin, Zainal; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The rapid growth of using blog in teaching and learning activity becomes new trends in educational world. Many researchers have reported a number of benefits of using blog as a powerful tool in enhancing students’ writing skills. The purpose of this study is to describe the students’ perspective on the use of blog for English writing learning and to find out the problems faced. The sample were the second semester students of teaching learning with ICT class which selected based on the returned questionnaires. The study showed that the students had positive attitude toward blog in improving their awareness in writing blog content to blog. Based on the research findings, the dimension of blog encourages writing skills practice achieved the highest responses, which had two highest percentages of the questionnaire items, there were item number 8 (85%) and number 9 (86.67%) which categorized as Very High. It also found 5 general problems that students faced, they were the problems in designing a blog (30.51%), the internet connection problem (22.03%), lack of ideas (20.33%), lack of grammar and vocabulary (20.33%), and the absence of feedback (6.8%). Keywords: Students’ Perspective, Blog, English Writing Learning Abstrak: Pesatnya pertumbuhan penggunaan blog dalam kegiatan belajar mengajar telah menjadi tren baru dalam dunia pendidikan. Telah banyak peneliti yang melaporkan kelebihan dalam penggunakan blog sebagai sebuah sarana yang sangat kuat dalam meningkatkan kemampuan menulis para siswa. Tujuan dari penelitian ini adalah untuk menggambarkan pendapat siswa akan kegunaan blog untuk belajar menulis bahasa Inggris dan untuk mencari tahu tentang masalah yang mereka hadapi. Sampel penelitian ini adalah 36 mahasiswa semester 2 dari kelas teaching learning with ICT yang dipilih berdasarkan data kuesioner yang dikembalikan. Penelitian ini menunjukkan bahwa para mahasiswa memiliki sikap yang positif terhadap blog dalam meningkatkan kesadaran mereka dalam menulis isi blog. Berdasarkan dari hasil penelitian, dimensi blog mendorong berlatih menulis bahasa inggris memperoleh respon tertinggi, yang memiliki 2 nomor kuesioner dengan persentase tertinggi, yakni nomor 8 (85%) dan nomor 9 (86.67%) yang dikategorikan Sangat Tinggi. Ditemukan juga 5 masalah utama yang dialami oleh mahasiswa, yakni masalah dalam mendesain blog (30.51%), masalah koneksi jaringan internet (22.03%), kekurangan ide (20.33%), kurang dalam tata bahasa dan kosakata (20.33%), dan tidak adanya respon (6.8%). Kata kunci: Pendapat Siswa, Blog, Pembelajaran Menulis Bahasa Inggris